Challenges and prospects: women's education in contemporary Afghanistan - Hasin, Basir Ahmad; Ayoubi, Mir Mohammad; Ahmad Shayan, Nasar (Frontiers in Global Women's Health, 2025)
Since the fall of the republic government in Afghanistan on August 15, 2021, the situation for women's education has regressed drastically. This article explores the multifaceted impact of Afghanistan's Current DeFacto government policies on women's educational opportunities. With a historical overview of women's rights in Afghanistan, this article delves into the current restrictions imposed by the regime, including the ban on women's higher education and the limited scope of semi-higher education. This highlights the significant challenges faced by Afghan women, such as cultural barriers, economic hardships, and restrictive policies on women's rights. The article also discusses potential solutions, including international pressure, infrastructure development, and cultural shifts towards a more inclusive interpretation of Islam. By examining these factors, this article aims to provide a nuanced understanding of the ongoing struggle for women's rights and education in Afghanistan while emphasizing the resilience of Afghan women and the crucial role of global advocacy in supporting their fight for equality.